Diskursus Aliran-aliran Filfsafat Pendidikan dalam Pengembangan Kurikulum Pendidikan Agama Islam - Umam Addzaky, Khoirul; Sukiman (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2024)
This study aims to examine the influence of various schools of educational philosophy on the development of Islamic Religious Education curriculum. The research method used was a literature study of various literature sources related to the schools of education philosophy and Islamic Education curriculum. The results showed that there are several main philosophical schools that influence the development of Islamic Education curriculum, such as essentialism, perennialism, progressivism, and reconstructionism. Each of these schools provides a different perspective on the objectives, content, methods, and evaluation of PAI learning. The PAI curriculum needs to be developed by considering the strengths and weaknesses of each of these philosophical schools. The conclusion of this study is that the development of PAI curriculum cannot be separated from the discourse of educational philosophy schools. A comprehensive understanding of the various philosophical schools will help curriculum designers in formulating objectives, selecting content, methods, and evaluations that are appropriate for effective and meaningful PAI learning. Keywords: Philosophy of Education, PAI curriculum, curriculum development